Higher-Order Generalized Invexity in Control Problems. (26th May 2011) - Padhan, S. K.; Nahak, C.
Abstract : We introduce a higher-order duality (Mangasarian type and Mond-Weir type) for the control problem. Under the higher-order generalized invexity assumptions on the functions that compose the primal problems, higher-order duality results (weak duality, strong duality, and converse duality) are derived for these pair of problems. Also, we establish few examples in support of our investigation.